PENINGKATAN PENYELARASAN AGILITY PERANCANGAN KEGIATAN AKADEMIK TERHADAP IMPLEMENTASI KALENDER AKADEMIK ONLINE YANG SESUAI STANDART KUALITAS BERDASARKAN DOMAIN COBIT YANG TERKAIT - Ratih Ayuninghemi; Prawidya Destarianto (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
Determination of the academic calendar is a very important process in an educational institution. Because with the academic calendar and schedule of activities will be organized and on time and on target. Academic calendar can also be used as a plan for future educational activities. On the Tools COBIT 4.1 or Control objectives for Information and related Technology there are several domains related to support the creation of Business Goal (BG) improving the efficiency of the academic activities of the students are PO8 and PO10. In this study conducted a measurement or measure the maturity of a prose IT support business processes for alignment between BG Process Efficiency and IT Activity Goal Submission of draft and Quality Standards and expense budget. After the measurement of maturity (Maturity) before and after the SPO added IT to support business processes and are also into the two domains COBIT as guidelines. The results of the comparison measure for domain PO8 maturity and PO10 significant increase of maturity is up 1 level so that the use of IT to support SOP Business Process indeed very important role.